Inovações em serviços informacionais na Biblioteca Pública do Amazonas - Souza, Ingrid Travassos (Brasil, 2022)
This work discusses innovation in services at the Public Library of Amazonas.With the general objective, to examine the existence of barriers and facilitators to implement and offer innovative information services in this environment. The specific objectives seek to characterize these services, identify the difficulties and facilities to implement them, diagnose the current situation of the public library in the state of Amazonas regarding the offer of innovative services and suggest improvements. As for the methodological procedures, it is an applied research, whose objectives are descriptive and exploratory, with a qualitative approach, starting from a bibliographic research, then it assumes the characteristics of a case study. Based on the results obtained, it is possible to identify that the main barriers to innovation are the lack of external investments, in favor of the acquisition of products to implement an adequate structure of technological services in this environment. The results point to partnerships with public organizations and other sectors as the greatest facilitator, as well as the motivation of the team for the use of new technologies. It concludes that the public library as a service provider needs to be constantly innovating and adapting its processes to deliver quality products that meet the demand of the community it serves.